An Analysis of the Deixis Used in the Bourne Identity Movie’s Script - Mohamad, Mohamad; Sujito, Sujito (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This research studies the form and the reference of the deictic words. The objective of this research is finding the form and the reference of deictic words used in the Bourne Identity script movie. In this research the writer uses the categories of deixis promoted by Levinson (1983). To conduct this research the writer uses observation and documentation method to collect the data’s needs. The observation is done by watching the film in several times. In order to obtain the objective mentioned, the data is gathered in the form of conversation excerption. After that, the writer analyses the deixis forms in the discourse of deixis by exploring the various kinds of deictic words phenomenon. In finding the meaning of deictic words the writer uses the Halliday’s concept of situational context as its instrument. The study shows that 1) there are five forms of deixis appears: there are 18 (26,45 %) of deictic words appear in person deixis, 16 (23,58 %) appear in place deixis, 10 (14,69 %) appear in time deixis, 11 (16,09 %) appear in social deixis and 13 (19,08 %) appear in discourse deixis form. 2) the reference can be explored that person deixis has we inclusive of addressee, we exclusive of addressee and reversal deictic. Deictic words in place deixis refers to location of the speaker at CT, point or location gesturally indicates, distal or proximal dimension from the speaker, proximal dimension to addressee at RT and how thing is where the addressee is. Deictic words of time deixis refer to past, present and future time. Deictic words in social deixis refer to absolute and relational social standing. Deictic words in discourse deixis refer to token reflexive and switch reference.